(untitled) (Memorias Sifored - Encuentros Educación UAN, 2023)
This work is the product of an alternate study as a result of two diagnostic approaches obtained from normal school students, future basic education teachers who are being trained in Mexico and Colombia. The purpose is to know the availability of resources, their knowledge and level of digital competence, as well as the use of ICT during their academic training. The methodology implied applying alternately because it was not at the same time, but the same Likert-type survey, to students of Normal schools from both countries. It was possible to reach conclusions that suggest common and relevant intervention measures for their training or even strengthen the respective academic preparation. The sampling was first applied (in June 2019) to 144 of 172 students (82.28%) of the Normal School for Educators of Arandas (ENEA), in the state of Jalisco, Mexico and (in August 2023) to 126 of 174 (72.41%) from the Escuela Normal Superior de Bucaramanga (ENSB), department of Santander in Colombia. Among the objectives, the following stand out: Evaluate the integration of ICT, availability of mobile or fixed resources, development of skills for the collection, self-management of knowledge, consumption, treatment and evaluation of information carried out by future educators from both countries.